The The Legal Challenges to Regulate New Energy in Indonesia: A Context of Green Legislation Vs State Control - Harris, Rahadyan Fajar; Wahyuni, Indria; Prihatiningtyas, Wilda (Universitas Negeri Semarang, 2023)
The Legislation of Indonesian New Energy and Renewable Energy Law (RUU EBET) received a negative response from various circles of society and academia. Main concept of the EBET Bill as green legislation is expected could encourage the energy transition and low-carbon development by reducing fossil energy and increasing the role of renewable energy. However, the internalization of new energy sources in the formulation of the EBET Bill, which is a product of fossil energy derivatives, is considered to hinder the energy transition process, so it is encouraged to be abolished. Nevertheless, the academic paper of the EBET Bill actually reveals that there is a national interest that is also urgent to be regulated in the EBET Bill, which is state control of new energy sources whose governance is still unclear. Therefore, this paper aims to explain the juridical conflict in the position of the EBET Bill as green legislation and at the same time as an instrument of state control over natural resources. The method used is normative juridical with statutory and conceptual approaches. The results of the research show that the EBET Bill should have two complementary goals, namely mitigating climate change through accelerating the energy transition and managing new energy sources that are still not organized in an orderly manner. The two goals are not to contradict one another, but serve as mutually reinforcing roadmaps. Keywords EBET Bill, Green Legislation, New Energy Source, New Energy, State Control.